Sustainability of e-waste Management: Egypt case study - Mohamed, Ahmed Tarek (AUC Knowledge Fountain, 2019)
The amount of electronic waste generated globally is alarming especially that it is on the rise. The impact of the generated amounts is not only Environmental. The electronic waste sector is unregulated in most developing countries; this results in the informal sector being heavily involved in managing and handling it. Due to the lack of regulations, informal handlers are exposed to hazardous materials that affect both their health and health of the communities living in their proximity. Moreover, the informal sector involves illegal child and women labour under harsh conditions. In addition to the social impact, the lack of regulations leads to missing major economic opportunities associated with developing a recycling industry for the safe handling and material recovery from the generated e-waste volumes. Electronic waste may contain up to 60 different materials including precious and rare-earth metals with an estimated equivalent economic value of 48 billion Euros (Baldé, Wang, Kuehr, & Huisman, 2015; Tansel, 2017). Egypt is one the countries which lack policies and regulations dedicated to e-waste, hence the Egyptian economy is missing the economic potential and job creation opportunities associated with developing the e-waste sector as well as facing major Environmental and health challenges due to the improper handling of the generated amounts. This thesis investigates the current situation of e-waste in Egypt through interviews with major stakeholders in the sector as well as a questionnaire. The thesis then proposes an adapted guideline for the sustainable management of e-waste in Egypt. The guideline is based on the international regulations and guidelines especially those of countries similar to the Egyptian socioeconomic context. Finally, the possibility of upcycling the rejects produced from the e-waste recycling processes is tested. Nonmetals represent around 70% of the total weight of the generated e-waste; these nonmetals include fiberglass and resins which are used in the manufacturing of PCBs (Kaya, 2016). In the Greater Cairo Area only, it is estimated that around 150 ton/year of PCBs are generated (Fathya Soliman & Mounir Boushra, 2017). Thus, the achieved results from upcycling the PCB powder into a composite material, which can replace marble to be used for tabletops or tiles, were a step ahead to realizing sustainable e-waste rejects handling. The produced material has an average flexural strength of about 1773 MPa compared to 1431 MPa for marble and the weight loss during abrasion test of the produced materials was between 0.13%-1.5% compared to about 8.8% for marble.